Integration of project management services for International Engineering, Procurement and Construction projects. Issue 2 (15th February 2021) - Amirtash, Parisa; Parchami Jalal, Majid; Jelodar, Mostafa Babaeian
Abstract : Purpose: International Engineering, Procurement and Construction (IEPC) projects deliver complex and critical infrastructure and construction projects. However, these projects face multiple challenges, especially in foreign construction markets, to the main contractors. The purpose of this article is to develop a tool for effective implementation of project management services for these international projects through upskilling and incorporate local expertise. Accordingly, the employment of a Native Project Management Consultant (NPMC) by the main contractor is proposed and investigated. Design/methodology/approach: A three-stage research method was employed for triangulation of knowledge. Initially, a comprehensive literature review was carried out to examine the theoretical foundations of the study. The concepts were further explored through a survey and expert interviews. The study was performed in Iran as the host nation of multiple IEPC projects. Findings: It was found that NPMC involvement has a significant contribution to the success of nearly all project management areas in IEPC projects. However, quality, schedule and budget management were the top-ranked areas. The study combines the results of previous studies with the interviews and questionnaire to create a tool designed to capture strategy actions and detailed activities designed to build capabilities in IEPC teams through the involvement of NPMCs. Practical implications: A practical tool is developed which aims to enhance NPMC integration into IEPC projects. The tool is in-line with the project management concept of work-breakdown structure; which is understandable by project stakeholders. Originality/value: The employment of NPMCs, and their potential role in IEPC projects has not been formally investigated and guidelines for such collaborations do not exist. The current study provides a platform for regulating such facilitators and enhancing project success.